Meta-analysis of anti-muscarinic receptor type 3 antibodies for the diagnosis of Sjögren syndrome. - Chuiwen Deng; Chaojun Hu; Si Chen; Jing Li; Xiaoting Wen; Ziyan Wu; Yuan Li; Fengchun Zhang; Yongzhe Li (PLoS ONE)
Purpose To conduct a meta-analysis to evaluate the diagnostic value of anti-muscarinic receptor type 3 (M3R) antibodies in Sjögren syndrome (SS). Methods Two databases, PUBMED and the Cochrane Library, were systematically searched. Approximately 2,000 participants from several studies were included in this research. STATA 11.2 software and Meta-DiSc 1.4 was used to conduct the meta-analysis. Results Eleven studies were included in the meta-analysis. The pooled DOR was 13.00 (95% CI, 6.00-26.00). The sensitivity was 0.43 (95% CI, 0.28-0.58) and the specificity was 0.95 (95%CI, 0.91-0.97). The LR+ and LR- were 7.90 (95% CI, 4.70-13.40), 0.61 (95% CI, 0.46-0.79), respectively. The AUC was 0.89 (95% CI, 0.86-0.92). Conclusion The anti-M3R antibody had high specificity but relatively low sensitivity for the diagnosis of SS.